Kebijakan Bebas Visa Kunjungan Menghilangkan atau Melestarikan Kearifan Lokal Bali - Intan Parameswari Anak Agung Ayu (Department of International Relations, Hasanuddin University, 2021)
This study was conducted to see whether the Indonesian government's policy to increase tourist visits will eliminate the values ​​of local wisdom and reduce people's welfare or vice versa. Furthermore, this paper also examines whether there is a role that the government can take to improve the welfare of the Balinese people and protect local values ​​as the unique attraction of Bali as the Island of the Gods. The findings of this research found that the high competition between countries in order to attract tourist visits to their country has caused Indonesia to start thinking and seriously reviewing various ways to further increase the number of tourists visiting Indonesia. Bali, as a tourist destination, is strongly encouraged to be able to increase the number of tourist visits every year. However, the question is whether the government is capable enough to encourage the growth of this sector without ignoring many conflicting effects that can arise, one of which is the increasing number of tourists in quantity but not accompanied by the quality of tourists and their purchasing power in this country. Another thing in terms of language problems, for example, tourists visiting Bali are mostly from China. Related to this, our society needs to work hard to be able to adapt and have good Chinese language skills in order to treat Chinese tourists. However , in practice many tour guides come from outside Bali, causing concerns and feelings of competition for the local Balinese people who work in this field. Penelitian ini akan mengkajian mengenai apakah kebijakan ini akan menghilangkan atau mampu melestarikan nilai-nilai kearifan lokal yang ada hingga kesejahteraan masyarakat lokal serta apakah ada peran yang dapat dilakukan pemerintah untuk melindungi masyarakat lokal serta nilai-nilai agar tentu dapat tetap dilestarikan sebagai satu daya Tarik khas Pulau Dewata. Temuan dalam penelitian ini ada;ah bahwa tingginya persaingan antar negara yang menyebabkan Indonesia mulai memikirkan bagaimana untuk meningkatkan jumlah wisatawan yang datang ke Indonesia terus dikaji. Bali khususnya sebagai daerah pariwisata menjadi daerah yang begitu didorong untuk mampu setiap tahunnya terus meningkatkan jumlah wisatawannya. Namun yang menjadi pertanyaan, apakah pemerintah mampu mendorong perekonomian di sektor ini tanpa melihat banyak efek yang dapat muncul, salah satunya adalah jumlah wisatawan yang meningkat secara kuantitas tidak diiringi dengan kualitas wisatawan yang datang serta daya beli mereka di negara ini. Hal lainnya ialah wisatawan yang banyak datang ialah wisatawan asal negara Tiongkok yang mana dari sisi Bahasa masyarakat kita perlu berupaya keras untuk beradaptasi dalam sisi Bahasa untuk dapat mentreat wisatawan yang datang yang pada prakteknya banyak tour guide yang berasal dari luar bali yang perlu didatangkan sehingga menimbulkan kekhawatiran bagi masyarakat lokal bali yang merasa tersaingi.